Patterns of Cytogenomic Findings from a Case Series of Recurrent Pregnancy Loss Provide Insight into the Extent of Genetic Defects Causing Miscarriages - Autumn DiAdamo; Hongyan Chai; Mei Ling Chong; Guilin Wang; Jiadi Wen; Yong-Hui Jiang; Peining Li (Global Medical Genetics)
Background A retrospective study was performed to evaluate the patterns of cytogenomic findings detected from a case series of products of conception (POC) in recurrent pregnancy loss (RPL) over a 16-year period from 2007 to 2023.